Stylistic and Rhetoric Elements on Memes in Education Context: A Critical Discourse Analysis - Guntar, Muhammad; Husein, Rahmad; Pulungan, Anni Holila (Faculty of Humanities, Universitas Jenderal Soedirman, 2024)
In this digital age, the presence of internet memes becomes a common way to share information online. People may use different stylistic and rhetoric elements to communicate their ideas and convey a particular meaning. This paper aimed to analyze stylistic and rhetoric elements employed in the selected memes in education context by using Van Dijk Critical Discourse Analysis. The data were forty memes related to education which were collected from four Instagram groups, namely itb.receh, school_life memoriess, 9gag.com, and memeindonesia.real. This research utilized descriptive qualitative method. The result showed that in stylistic, the most dominant dictions used were slang and denotative. The high frequency of using slang is done as a strategy to express a sense of familiarity to audiences and to show portrait of daily basis situation in students’ lives, while the use of denotative dictions conveys clear understanding and avoid misinterpretation toward these memes. Furthermore, in rhetoric elements, no metaphor is found in the selected memes while graphics is mostly used in the memes to highlight important parts. It was delivered through the production of words in bigger size, bold, different colour, different type of fonts, words which are crossed out, and the use of emoticon. Graphic provides a visual representation for audiences and these highlighted words help them comprehend messages and values which the writer is trying to deliver.